Electrospun Poly (Ionic Liquid) Membrane Based Solar Cell For Sustainable Clean Energy - Thomas, Mini; Rajiv, Sheeja (European Publisher, 2019)
The quest for sustainable and clean energy production has incentivized the development of solar cell technology. Dye-sensitized solar cells (DSSCs) have a significant influence on this revolution. Efficient and stable electrolyte systems are necessary for the outdoor application of DSSCs. An innovative polymeric ionic liquid (PIL), poly 3-decyl-vinyl imidazolium methyl methacrylate tetrafluoroborate was synthesized, characterized and blended with poly (ethylene oxide) (PEO). The polymer fibrous membranes have been fabricated by electrospinning technique, which were used as the electrolyte for DSSCs. Electrospun nanofibrous membrane possess high porosity and excellent specific surface area that can imbibe large amount of liquid electrolyte into its interconnected network structure. These membranes were studied by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), differential scanning calorimetry (DSC) techniques and investigated their physical characteristics such as porosity, electron uptake and ionic conductivity. Photovoltaic and electrochemical effects have been examined. PEO/PIL membrane was compared with PEO for their efficiency. From the result, it was seen that PEO/PIL membrane exhibited superior power conversion efficiency (η), excellent ionic conductivity and better long term stability compared to cell with liquid electrolyte and PEO membrane. This novel PEO/PIL membrane based electrolyte in DSSC showed promising potential for the production of clean energy.